Factores motivacionales de los trabajadores de una supertienda de cadena de las sedes Montenegro y Quimbaya - Echeverri Sánchez, Adolfo (Universidad Antonio Nariño, 2021)
Different aspects of organizational dynamics can be affected by motivation, including staff turnover, job performance, organizational climate, productivity and competitiveness. For this reason, a quantitative-descriptive study was proposed to investigate the motivational factors of the personnel that work in a chain superstore with headquarters in Montenegro and Quimbaya - Quindío, composed of 61 members between 18 and 56 years of age or more, men and women from different areas of the company. The CMT (Work Motivation Questionnaire) was applied to investigate the internal and external dimensions of work motivation and the preferred means of obtaining benefits, and the results were analysed according to their socio-demographic characterisation. The results indicated that internally employees were more motivated by recognition and affiliation, externally by salary and the preferred means of obtaining compensation at work was requisitioning.